Enhancing Learners' Engagement in Araling Panlipunan through Gamification: A Philippine Case Study - Kenneth Panga; Marjorie C. Doroin; John Marc Campo; Cherrynel Bohayo; Silva P. Oxidental (MASI Mandiri Edukasi, 2025)
Learner disengagement remains a pressing concern in Araling Panlipunan (Social Studies) classes, where the subject is often viewed as monotonous and detached from students' interests. This action research investigated the potential of gamification as an innovative approach to enhance learners' engagement in Araling Panlipunan. Conducted during the 2024–2025 school year, the study involved a selected Grade 10 class consisting of forty (40) learners at San Rafael National High School in Tigaon, Camarines Sur, Philippines. A single-group research design was employed, and purposive sampling was used to select participants from a section with relatively low classroom engagement and academic performance. A five-week intervention was implemented, integrating game-based elements such as point systems, leaderboards, and reward mechanisms into Araling Panlipunan lessons. Learner engagement was tracked through structured scoring for participation and the quality of responses, supported by weekly leaderboards that fostered healthy competition. The pre-intervention results revealed a Mean Percentage Score (MPS) of 44.44% in engagement-related indicators, classified as